REPRESENTASIPEREMPUAN DALAM IKLAN CITRA DI MEDIA CETAK (Studi Analisis Semiotika lklan Pemutih Kulit CITRA , Edisi 2-15 Januari 2008 di Majalah Smart CHIC) - Pratiwi, Ayuningtyas (Universitas Prof. Dr. Moestopo (Beragama), 2010)
The use of mass media become a tool of the most effective, efficient and quick way to inform the company in a product or service to the society s, and was mostly done by the company to rnenggunakan rnassa media as a tool to promote products or services to be offered to the public, one of which is print media that this is a magazine in ha]. Most magazines are published mernang comfort women. One reason is because this segment is potential for pernasaran certain products such as cosmetics, clothing, accessories,furniture, cleaning tools rurnah, and others. Womenhave all the beauty that can be used as an advantage to attract anyone who saw it. Startingfrom the long black hair, beautiful face, smooth, tall, slim body and smooth-skinned and white. The author would like to investigatefurther how a beauty product, in this case, Citra Body Lotion, representingthe woman as a model of beauty advertising.